1973
DOI: 10.1111/j.1537-2995.1973.tb05458.x
|View full text |Cite
|
Sign up to set email alerts
|

In Vitro Analysis of Platelet Function During Storage of Platelets from Plasmapheresed Donors

Abstract: Several in vitro platelet function assays were examined. Two units of platelets from each of ten volunteer donors were obtained by plasmapheresis, stored three days, and examined by various functional parameters. The second unit of platelets from an individual had generally lower functional parameters than the first, suggesting a subtle physiological change in the donors' circulation between the time of drawing the first and second units. For in vitro comparisons, this difference was overcome by a pooling proc… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
3
0

Year Published

1975
1975
1999
1999

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 14 publications
(3 citation statements)
references
References 8 publications
0
3
0
Order By: Relevance
“…Other investigators [10,11] have reported measurements of PF3 in platelet concentrates (PC), but the assays employed were a test of the ability of platelets to respond to a challenge (e.g., incubation with kaolin) rather than a measurement of the PF3 activity already expressed in the sample. Also, the Stypven PF3 assay used by Champion [12] to study stored platelets is known to respond nonspecifically to neutral phospholipids and lipoproteins [13] , and, therefore, cannot be relied upon for comparison of PF3 levels between different concentrates.…”
Section: Introductionmentioning
confidence: 99%
“…Other investigators [10,11] have reported measurements of PF3 in platelet concentrates (PC), but the assays employed were a test of the ability of platelets to respond to a challenge (e.g., incubation with kaolin) rather than a measurement of the PF3 activity already expressed in the sample. Also, the Stypven PF3 assay used by Champion [12] to study stored platelets is known to respond nonspecifically to neutral phospholipids and lipoproteins [13] , and, therefore, cannot be relied upon for comparison of PF3 levels between different concentrates.…”
Section: Introductionmentioning
confidence: 99%
“…Several aspects of the in vitro function of platelets stored as platelet concentrates and destined for transfusion therapy have been studied in the past [1,9,14,27,29,37]. Platelets suspended and stored in their own plasma quickly lose the capacity of agonist-induced aggregation [24,28,36].…”
Section: Discussionmentioning
confidence: 99%
“…pH, p02 and pC02, aggregation and adhesivity of stored platelets have also been investigated in order to assess our working conditions. A simple and reliable in vitro test for predicting the posttransfusion survival and hemostatic effectiveness of preserved plate lets would be extremely useful in quality control and in assessing methods of platelet concentrate (PC) preservation.Widely used tests for platelet viability in clude the clot retraction, promoted by sen sibilized platelets [1], the photometric mea surement of ADP-induced aggregation [6,9,12], adhesivity to glass surfaces [4,6], the hypotonic shock response (HSR) [3,7,15], and serotonin uptake [5,10]. Among the methods listed, only serotonin uptake and HSR have been shown to correlate with 1 We are indebted to Prof. P. Lundsgaard-Hansen for invaluable help in performing statistical anal ysis and critical reading of the manuscript.…”
mentioning
confidence: 99%